2021
DOI: 10.1002/ptr.7252
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lemon balm (Melissa officinalis L.) on depression and anxiety in clinical trials: A systematic review and meta‐analysis

Abstract: Outcomes were classified as primary, including depression or anxiety, and secondary as side effects of lemon balm. Primary outcomes were considered in acute or chronic manifestations. | Information sourcesEnglish databases, including Cochrane Library, Web of Sciences, Scopus, PubMed, ProQuest, Trip Database, Clinical Key, and Google Scholar, and Persian databases, including Magiran, Iranmedex, Iran Doc, and SID, were searched until October 30, 2020, without time limitation. The cited references of the selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Interestingly, citrus aurantium L . significantly ameliorated anxiety and did not interfere with physiological levels of melatonin and corticosterone ( 71 ). Thus, it could be reasonably inferred that citrus aurantium L .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, citrus aurantium L . significantly ameliorated anxiety and did not interfere with physiological levels of melatonin and corticosterone ( 71 ). Thus, it could be reasonably inferred that citrus aurantium L .…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Moaca et al studies concluded that rosmarinic acid (RA) a well-known phenolic compound from M. officinalis was responsible for the plants antimigratory effects. 39,40 Jahanban-Esfahlan et al evaluated the anti-tumor effect of Lemon balm different extracts, on H460 and two other cancer cell lines; reporting the ethanol extract as the most effective, and H460 cell line as the most affected cells. 35 They concluded that M. officinalis dose-dependently affected the cell cycle profile of H460 cells.…”
Section: Melissa Officinalismentioning
confidence: 99%
“…Specifically, St. John's Wort alters Melissa officinalis L. is a medicinal plant traditionally used in various ethno-medical systems, particularly in Traditional European Medicine and Traditional Iranian Medicine for the treatment of various diseases. It is also widely used as a vegetable and to flavor dishes [56]. Biological studies have shown that essential oil and extracts of lemon balm have natural components capable of determining pharmacological effects with potential clinical uses.…”
Section: Drug-natural Compound Interactions: Cyp3a4 Inhibitionmentioning
confidence: 99%